Unraveling the Intoxicating and Therapeutic Effects of Cannabis Ingredients on Psychosis and Cognition - Colizzi, Marco; Ruggeri, Mirella; Bhattacharyya, Sagnik (Frontiers in Psychology, 2020)
Research evidence suggests a dose-response relationship for the association between cannabis use and risk of psychosis. Such relationship seems to reflect not only an increased risk of psychosis as a function of frequent cannabis use, but also of high-potency cannabis use in terms of concentration of delta-9-tetrahydrocannabinol (∆9-THC), its main psychoactive component. This finding would be in line with the evidence that ∆9-THC administration induces transient psychosis-like symptoms in otherwise healthy individuals. Conversely, low-potency varieties would be less harmful because of their lower amount of ∆9-THC and potential compresence of another cannabinoid, cannabidiol (CBD), which seems to mitigate ∆9-THC detrimental effects. A growing body of studies begins to suggest that CBD may have not only protective effects against the psychotomimetic effects of ∆9-THC but even therapeutic properties on its own, opening new prospects for the treatment of psychosis. Despite more limited, evidence of the effects of cannabis on cognition seems to come to similar conclusions, with increasing Δ9-THC exposure being responsible for the cognitive impairments attributed to recreational cannabis use while CBD preventing such effects and, when administered alone, enhancing cognition. Molecular evidence indicates that Δ9-THC and CBD may interact with cannabinoid receptors with almost opposite mechanisms, with Δ9-THC being a partial agonist and CBD an inverse agonist/ antagonist. With the help of imaging techniques, pharmacological studies in vivo have been able to show opposite effects of Δ9-THC and CBD also on brain function. Altogether, they may account for the intoxicating and therapeutic effects of cannabis on psychosis and cognition.